American-Filipino marriages a descriptive study of twenty inter-racial problem marriages involving United States military personnel and Filipinos - Calhoun, John William 1919- (1955)
Inter-racial marriages between Filipino and American military personnel is the subject of this study. The writer attempted to isolate certain common factors which seemed to have contributed to problems and difficulties in these marriages. These conditions were then evaluated in order to determine the areas of conflict encountered in marriage to a member of another cultural and/or racial group. Some effort was also made to evaluate the conditions which seemed to cause the failure of the marriage as well as the special problems of adjustment necessary in marriage of this nature.